DAMPAK PELAKSANAAN PEMBELAJARAN DARING - Aditya Hendra Sulistyawan (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2021)
Online learning is learning that is carried out using the internet as a a place to transmit knowledge. This learning can be done at home anywhere and without having to meet face to face. In the era of technological development. Online learning is getting more sophisticated with more applications and features make it easier for users. Not bound by time and carried out without meeting face to face advantages of online learning that can be used by educators. As happened when In this case, online learning is the only most effective option used for the learning process to keep going. Indonesia applies social distance in all aspects of life, including the world of education. Therefore, learning online can be said to be the only learning option that can be done by educators to improve the quality of learning in Indonesia.